Oral Mesenchymal Stem/Progenitor Cells: The Immunomodulatory Masters. (25th February 2020) - Zhou, Li-li; Liu, Wei; Wu, Yan-min; Sun, Wei-lian; Dörfer, C. E.; Fawzy El-Sayed, K. M.
Abstract : Oral mesenchymal stem/progenitor cells (MSCs) are renowned in the field of tissue engineering/regeneration for their multilineage differentiation potential and easy acquisition. These cells encompass the periodontal ligament stem/progenitor cells (PDLSCs), the dental pulp stem/progenitor cells (DPSCs), the stem/progenitor cells from human exfoliated deciduous teeth (SHED), the gingival mesenchymal stem/progenitor cells (GMSCs), the stem/progenitor cells from the apical papilla (SCAP), the dental follicle stem/progenitor cells (DFSCs), the bone marrow mesenchymal stem/progenitor cells (BM-MSCs) from the alveolar bone proper, and the human periapical cyst-mesenchymal stem cells (hPCy-MSCs). Apart from their remarkable regenerative potential, oral MSCs possess the capacity to interact with an inflammatory microenvironment. Although inflammation might affect the properties of oral MSCs, they could inversely exert a multitude of immunological actions to the local inflammatory microenvironment. The present review discusses the current understanding about the immunomodulatory role of oral MSCs both in periodontitis and systemic diseases, their "double-edged sword" uniqueness in inflammatory regulation, their affection of the immune system, and the underlying mechanisms, involving oral MSC-derived extracellular vesicles.